98 Assessment of Endogenous Thrombolysis Predicts Cardiovascular Risk in Patient with ST-elevation Myocardial Infarction. (3rd June 2016) - Farag, Mohamed; Srinivasan, Manivannan; Wellsted, David; Sullivan, Keith; Gorog, Diana A
Abstract : Background: Increasingly potent antithrombotic medications have been developed to reduce thrombosis in patients presenting with ST-elevation MI (STEMI). These reduce thrombosis but increase bleeding risk. Identification of STEMI patients at high risk of recurrent thrombosis could allow targeted treatment with potent antithrombotic medications, with less potent agents in others, to reduce bleeding. We aimed to assess the risk of thrombosis by assessing platelet reactivity, as well as the efficacy of endogenous thrombolysis, the innate ability to dissolve thrombus. Methods: In 150 patients with STEMI, global thrombotic status was assessed at baseline, immediately before primary percutaneous coronary intervention (PPCI), at hospital discharge and at 30 days. Peripheral, non-anticoagulated blood was tested using the point-of-care Global Thrombosis Test, which assesses the time to form an occlusive thrombus under high shear (occlusion time, OT), and the time to dissolve this in vitro formed thrombus, through endogenous thrombolysis (lysis time, LT). Results: Impaired endogenous thrombolysis (prolonged LT ≥3000s), seen in 9% of patients pre-PPCI, was significantly associated to the occurrence of major adverse cardiac events at 30 days (HR: 3.26, 95% CI: 2.32–29.19, p = 0.004), driven by cardiovascular death (HR: 3.12, 95% CI: 3.82–35.23, p < 0.001). Enhanced (rapid) endogenous thrombolysis (median LT 1040s [IQR: 940–1105]s), seen in 17% of patients pre-PPCI, was associated with spontaneous coronary reperfusion, ST-segment resolution, TIMI-2/3 flow pre-PPCI, favourable outcomes and longer baseline OT (515 ± 178 vs. 385 ± 177, p < 0.001). Pre-PPCI OT was shorter in those with recurrent myocardial infarction and stroke than those without (244 ± 130s vs. 414 ± 183s, p = 0.025). OT was prolonged at hospital discharge (500 ± 141s vs. 407 ± 184s, p < 0.001) and 30 days (577 ± 131s vs. 407 ± 184s, p < 0.001) compared to baseline, likely due to the effects of antiplatelet medication. Conclusions: In patients with STEMI, endogenous thrombolysis, when impaired, is associated with increased cardiovascular risk, and when enhanced, with spontaneous reperfusion and favourable outcomes. Identification of impaired endogenous thrombolytic status may serve as a novel biomarker to identify high-risk patients who may benefit from enhanced pharmacotherapy to reduce adverse events.